2018
DOI: 10.1002/agr.21563
|View full text |Cite
|
Sign up to set email alerts
|

Cooperatives, contract farming, and farm size: The case of tomato producers in Nepal

Abstract: This study investigates the impact of contract farming (CF) through cooperatives in tomatoes on employment and economic performance of smallholders in a low‐income developing country. Using farm‐level data from Nepal and a nonparametric matching estimator, the study finds a negative and significant effect of CF on employment. However, CF through cooperatives has a positive and significant impact on profits, and yield. We find that small farms (≤0.51 ha) with contracts tend to gain in profits and yield per hect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 46 publications
1
33
0
2
Order By: Relevance
“…Using an endogenous switching regression approach, Mishra et al (2018a) reveal that farmer group membership enhances value chain participation and food security through white onion contract farming in India. A plethora of other studies also found that smallholder participation in agrifood value chains though farmer groups improves farm yields, household income and net farm income (e.g., Maertens and VandeVelde, 2017;Mishra et al, 2018b), prices received by group members, farm profit and gross income (e.g., Ma and Abdulai, 2017) and land and labor redistribution (e.g., Henderson and Isaac, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Using an endogenous switching regression approach, Mishra et al (2018a) reveal that farmer group membership enhances value chain participation and food security through white onion contract farming in India. A plethora of other studies also found that smallholder participation in agrifood value chains though farmer groups improves farm yields, household income and net farm income (e.g., Maertens and VandeVelde, 2017;Mishra et al, 2018b), prices received by group members, farm profit and gross income (e.g., Ma and Abdulai, 2017) and land and labor redistribution (e.g., Henderson and Isaac, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Very few studies have extended their analysis on how factors like output prices and labor inputs contribute to the improvement of smallholders welfare through CF (Bellemare, 2018;Benali, Brümmer, & Afari-Sefa, 2018;Mishra, Kumar, Joshi, & D'Souza, 2018a). Participation in CF generally evolves in response to market imperfections particularly that of labor inputs due to moral hazard and high monitoring costs in developing countries (Casaburi, Kremer, & Mullainathan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Such agreements can involve specification about the transaction only, such as product quality, delivery times, as well as sales price (marketing contract), or specifications related to production process, product quality, seed variety, chemicals used among others (production contract; Maertens & Vande Velde, 2017; Roussy, Ridier, Chaib, & Boyet, 2018). Contracting is important in facilitating farmers’ access to inputs, credit, and technology, as well as reduces risks associated with prices and markets (Kariuki & Loy, 2016; Mishra, Kumar, Joshi, & Dsouza, 2018). Buyers can prefinance smallholder farmers by providing them within puts, technology, and cash credit, and costs associated with these provisions are deducted from the final produce at the point of product delivery (Bellemare, 2012).…”
Section: Introductionmentioning
confidence: 99%